Announcement — The Paper Award of Tribology Online – - Masabumi Masuko (Japanese Society of Tribologists, 2014)
The Japanese Society of Tribologists is pleased to announce that the 2012 Paper Award of Tribology Online was awarded to:“Friction and Wear of Ferrous Materials in a Hydrogen Gas Environment,” by Kanao Fukuda, Masaaki Hashimoto, Joichi Sugimura, Vol. 6, No. 2 (2011) 142-147.and“The Effects of UV Irradiation on Z-Tetraol Boundary Lubricant,” by Robert J. Waltman, John Newman, Xing-Cai Guo, John Burns, Connie Wiita, Mina Amo, Vol. 7, No. 2 (2012) 70-80.The Award Medals were presented to the authors by Prof. Masabumi Masuko, the President of the Japanese Society of Tribologists, at the JAST Annual Meeting on 21st May, 2013.The Paper Award of Tribology Online is given annually to the author(s), either the JAST members or non-members, of the paper(s) judged as the best paper(s) published in Tribology Online (TROL) for the previous three years. All papers that appeared in TROL for the three years are reviewed by the JAST Awards Committee.